2015
DOI: 10.4081/jlimnol.2015.1097
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and levels of cyanotoxin nodularin from Nodularia spumigena in the alkaline and salty Lake Burdur, Turkey

Abstract: The occurrence of cyanobacteria species Nodularia spumigena and its toxin nodularin were studied in Burdur Lake, a saline alkaline lake with endemic fauna and a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nodularin (NOD) hepatotoxins are mostly known from the Baltic Sea. However, recently nodularin was found also in aquatic ecosystems in Turkey Sahindokuyucu Kocasari et al, 2015). Moreover, Nodularia spumigena Mertens ex Bornet & Flahault, a NOD-producer, was recently observed not only in brackish waters but also in freshwater lakes (Akcaalan et al, 2009).…”
Section: Occurrence Of Cyanobacteria and Cyanotoxins And Methods Formentioning
confidence: 99%
“…Nodularin (NOD) hepatotoxins are mostly known from the Baltic Sea. However, recently nodularin was found also in aquatic ecosystems in Turkey Sahindokuyucu Kocasari et al, 2015). Moreover, Nodularia spumigena Mertens ex Bornet & Flahault, a NOD-producer, was recently observed not only in brackish waters but also in freshwater lakes (Akcaalan et al, 2009).…”
Section: Occurrence Of Cyanobacteria and Cyanotoxins And Methods Formentioning
confidence: 99%
“…Nodularia spumigena, a cyanobacteria species account for cyanotoxin nodularin, has peaked in recent years and the lake has been plagued by excessive algal blooms in the shoreline (Figure 4). When Kocasarı et al [25] first reported the algal bloom event in 2015, there were no apparent fish kills in the Lake. However, it was noted by one of the authors (İskender Gülle, pers.…”
Section: Threatsmentioning
confidence: 99%